Temperature dependence, spatial scale, and tree species diversity in eastern Asia and North America - Wang, Zhiheng; Brown, James H.; Tang, Zhiyao; Fang, Jingyun (Proceedings of the National Academy of SciencesProceedings of the National Academy of SciencesProceedings of the National Academy of Sciences, 2009)
The increase of biodiversity from poles to equator is one of the most pervasive features of nature. For 2 centuries since von Humboldt, Wallace, and Darwin, biogeographers and ecologists have investigated the environmental and historical factors that determine the latitudinal gradient of species diversity, but the underlying mechanisms remain poorly understood. The recently proposed metabolic theory of ecology (MTE) aims to explain ecological patterns and processes, including geographical patterns of species richness, in terms of the effects of temperature and body size on the metabolism of organisms. Here we use 2 comparable databases of tree distributions in eastern Asia and North America to investigate the roles of environmental temperature and spatial scale in shaping geographical patterns of species diversity. We find that number of species increases exponentially with environmental temperature as predicted by the MTE, and so does the rate of spatial turnover in species composition (slope of the species-area relationship). The magnitude of temperature dependence of species richness increases with spatial scale. Moreover, the relationship between species richness and temperature is much steeper in eastern Asia than in North America: in cold climates at high latitudes there are more tree species in North America, but the reverse is true in warmer climates at lower latitudes. These patterns provide evidence that the kinetics of ecological and evolutionary processes play a major role in the latitudinal pattern of biodiversity.